2015
DOI: 10.1142/s0192415x15500469
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Colon Cancer Effects of 6-Shogaol Through G2/M Cell Cycle Arrest by p53/p21-cdc2/cdc25A Crosstalk

Abstract: Chemopreventive agents can be identified from botanicals. Recently, there has been strong support for the potential of 6-shogaol, a natural compound from dietary ginger (Zingiber officinale), in cancer chemoprevention. However, whether 6-shogaol inhibits the growth of colorectal tumors in vivo remains unknown, and the underlying anticancer mechanisms have not been well characterized. In this work, we observed that 6-shogaol (15 mg/kg) significantly inhibited colorectal tumor growth in a xenograft mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
(29 reference statements)
1
26
0
1
Order By: Relevance
“…Furthermore, by using HCT-116 and IEC-6 cells, we found that the impact of CELF1 on enterocyte proliferation is highly dependent on p53. Of note, a number of previous studies have revealed that ectopic overexpression of p53 induces G2 arrest in HCT-116 cells (42,43) and induces G1 arrest in IEC-6 cells (44,45). Likewise, our results indicated that ectopic overexpression of CELF1 exhibited the same impact on these cell lines as p53 did, and could be significantly by p53 silencing.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, by using HCT-116 and IEC-6 cells, we found that the impact of CELF1 on enterocyte proliferation is highly dependent on p53. Of note, a number of previous studies have revealed that ectopic overexpression of p53 induces G2 arrest in HCT-116 cells (42,43) and induces G1 arrest in IEC-6 cells (44,45). Likewise, our results indicated that ectopic overexpression of CELF1 exhibited the same impact on these cell lines as p53 did, and could be significantly by p53 silencing.…”
Section: Discussionsupporting
confidence: 80%
“…The anti-cancer effect of ginger on patients with colon cancer and other gastrointestinal cancers was emphasized in other studies (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 98%
“…Proliferation inhibition and apoptosis induction can be trigger by cell cycle arrest in cancer cells ( 26 ). Cdc2 and cyclin B1 are involved in controlling the G2/M checkpoint ( 27 ), and some anticancer-drugs induce G2/M arrest by deregulating the expression of cyclin B1 and Cdc2 ( 28 , 29 ). The results in the present study indicated that treatment of the prostate cancer cells with Scutellarin induced G2/M arrest which was mainly due to a decrease in cyclin B1 and Cdc2 expression.…”
Section: Discussionmentioning
confidence: 99%